Current advances and applications of online sample preparation techniques for miniaturized liquid chromatography systems - Cruz, Jonas Carneiro; Souza, Israel Donizeti de; Lanças, Fernando Mauro; Queiroz, Maria Eugênia Costa (Journal of Chromatography A, 2022)
•Miniaturized liquid chromatography has been applied in several research fields.•Online coupling of sample preparation techniques with miniaturized systems improve the analytical efficiency.•Online systems boost analytical performance and sensitivity.•Online miniaturized LC configurations, innovative sorbents, and applications are described. Miniaturized liquid chromatography (LC) has been recognized as one of the most important analytical methods in several research fields. Reduced analytical work-scale provides superior chromatographic resolution and decreases sample and organic solvent consumption. However, frequent clogging of tubing connections and use of small sample volumes are significant limitations when high throughput and sensitive analyses are required. Effective sample preparation could help to overcome these limitations. Online coupling of sample preparation techniques (such as column switching and in-tube solid-phase microextraction) with these miniaturized systems may result in more sensitive and reproducible analyses, improving analytical efficiency. This review describes the most common online miniaturized LC configurations, and the main applications of current online sample preparation techniques coupled to miniaturized LC systems in the bioanalytical, omics, and environmental areas. Relevant features, and challenges of these systems, and innovative sorbents, including restricted access materials, monoliths, and immunosorbents is also discussed.